Samakālīna Hindī kavitā - Asthānā, Avanīśa Kumāra (Goyala Pablikeśansa, 2020)
On trends and expressions of contemporary Hindi poetry.
Includes bibliographical references (pages 219-224)
Keywords: Hindi poetry; 20th century; History and criticism